Pengaruh Kepemimpinan Kharismatik dan Budaya Organisasi terhadap Sistem Pendidikan Pesantren Ulumuddin Kota Lhokseumawe - Indra Kurnia; Muhammad Anggung Manumanoso Prasetyo (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
The research aims to understand the significance of the influence of charismatic leadership and organizational culture on the pesantren education system. Additionally, the study analyzes other determinant factors affecting the education system in pesantren. The research employs a mixed methods approach, incorporating both quantitative and qualitative methods. This combination method utilizes a sequential explanatory type, where the initial phase involves a quantitative research method, which is then reinforced with a qualitative method. The study population consists of all teachers at the Ulumuddin pesantren in the city of Lhokseumawe, totaling 45 teachers. The sampling technique used is quota sampling. Data for the study was collected through questionnaires, structured interviews, and documentation. The results of this research show that charismatic leadership directly influences organizational culture, with a t-statistic value of 3.604 > t-table of 2.016, as determined by the pesantren education system. Meanwhile, the significance value of 0.000 < 0.05, or the level of significance is lower than the probability level, indicates there is a positive and significant influence between charismatic leadership and the pesantren education system through organizational culture at the Ulumuddin Pondok Pesantren in Lhokseumawe city.